Kekerasan Dalam Rumah Tangga (Sosialisasi UU Nomor 23 Tahun 2004 Tentang Penghapusan KDRT) - Disna Anum Siregar; Tri Reni Novita; M. Faisal Husna; Halimatul Maryani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service (PkM) activities have been carried out with the title domestic violence, socialization of law number 23 of 2004 concerning the elimination of domestic violence in Tanjung Harapan Village, Serba Jadi District, Serdang Bedagai Regency. The lack of knowledge among village residents regarding the legal consequences of domestic violence has an impact on the potential for family disharmony in the future. Therefore, families need to be provided with enlightened legal education in living family life in order to avoid violence in the family environment. The method used in PkM activities is in the form of legal education counseling/socialization which includes face-to-face lectures accompanied by question-and-answer discussions. The results obtained from this PkM activity have further enlightened and increased the understanding of the residents of Tanjung Harapan village that domestic violence can trigger prolonged marital breakdown and even divorce. The conclusion of this PkM activity material is that domestic violence is a violation of human rights and a crime against human dignity and is a form of discrimination. Violence in any form and carried out for any reason is a form of crime that cannot be justified and can be reported as a criminal act so that the perpetrator can be prosecuted